Alcohol use, vision therapy, children, mood … what predicts post-traumatic growth after concussion in women? - Martina Anto-Ocrah; Katherine Kenyon; Celestin Niyomugabo; Michael Chen; Jane Liebschutz; Katherine Snedaker (Frontiers in Global Women's Health, 2026)
Background Post-traumatic growth (PTG) refers to positive psychological change following a traumatic or life-altering event. Concussion, also known as mild traumatic brain injury(mTBI), results from a physical trauma that can lead to psychological outcomes such as post-traumatic stress disorder (PTSD) as well as PTG. Research indicates that PTG and PTSD occur at similar rates among individuals who have experienced concussion, consistent with findings across other trauma-exposed populations. While women often experience more difficult concussion recoveries than men, they often experience greater PTG after trauma. Understanding the factors that support PTG in women with post-concussion symptoms may help guide clinical care to both foster PTG, and identify individuals who may require more targeted recovery support. Objectives We examined how demographic, health behaviors, concussion-related, and mental health factors—as well as access to therapeutic services—relate to PTG in women. We also explored the association between PTG and traits such as resilience and flourishing following concussion. Methods A cross-sectional survey was conducted from November 10–13, 2023, among U.S.-based women living with persistent post-concussion symptoms. PTG was assessed using the Post-traumatic Growth Inventory (PTGI-X; cutoff: <75 = low PTG, ≥75 = moderate/high PTG), injury details, mood (PHQ-9, GAD-7), and persistent post-concussion symptoms (Rivermead Post-Concussion Questionnaire). Descriptive statistics compared groups. Logistic regression identified associated factors of PTG and estimated corresponding odds ratios. Results A total of 434 PINK Concussion members responded to the survey with 116 (27%) completing all questions. The mean PTG score was 70.0 (SD = 26.9; median = 71; range = 1–125). Just over half (51.7%, n = 60) had low PTG scores (<75), while 48.3% ( n = 56) had moderate-to-high PTG scores. High PTG was significantly associated with being African American/Black or Hispanic/Latino ( p = .007), multiparity ( p = .013), and having multiple young children at home ( p = .004). Low PTG participants were more likely to have sought multiple treatments ( p = .0244), and to have a history of alcohol use ( p = .025). Vision therapy was more common in the low PTG group (31% vs. 7%, p = .001), suggesting it may be linked to unresolved visual symptoms. A higher proportion of high PTG participants had returned to work (66% vs. 45%, p = .036). High PTG was also associated with greater resilience ( p = .005) and flourishing ( p = .005), with a positive correlation between these traits. Conclusion This exploratory study highlights key demographic and psychosocial factors linked to PTG in women recovering from concussion. Modifiable characteristics such as resilience, flourishing, and lifestyle stability, particularly return to work and absence of alcohol use—were associated with higher PTG, offering potential intervention targets and helping to identify individuals who may require more intensive post-concussion support.